Does Initial Cleft Lip Width Predict Final Aesthetic Outcome?. Issue 12 (December 2021) - Yang, Jenny F.; Smetona, John; Lopez, Joseph; Peck, Connor; Pourtaheri, Navid; Steinbacher, Derek M.
Abstract : Background: A natural aesthetic appearance of the lip and a favorable scar are essential goals of cleft lip repair. Wider clefts intuitively pose a greater technical challenge; however, the relationship between initial width and aesthetic outcome remains controversial. The current study aimed to determine whether lip adhesion can help wider clefts achieve safe, consistent aesthetic outcomes. Methods: A retrospective cohort study was conducted on unilateral cleft lip patients who underwent lip repair within a 2-year period by the senior author. Subjects were divided into three groups based on cleft severity: (1) wide complete clefts that required lip adhesion before definitive repair, (2) narrower complete clefts that did not require lip adhesion, and (3) incomplete clefts. Aesthetic outcomes related to the vermillion and upper lip scar were rated by 48 blinded observers. Statistical analysis was performed using Kruskal-Wallis and Mann-Whitney tests. Nasal outcomes were not assessed. Results: Seventeen patients were included in the study: five in group 1, six in group 2, and six in group 3. Patients with the widest clefts did not have inferior results compared with the other groups. In fact, they had statistically significantly higher aesthetic scores in all scar-related outcomes compared with those in groups 2 and 3 ( P < 0.0001). Conclusions: This study suggests that a wide cleft does not necessarily foreshadow a poor surgical outcome. In fact, wide clefts may have pleasing results, and the use of a staged lip adhesion approach can be useful for achieving the desired outcome in wider clefts.